Whom to lobby? Targeting in political networks - Thomas Groll; Anja Prummer (Queen Mary University of London, School of Economics and Finance, 2016)
We study lobbying in a setting in which decision-makers share resources in a network. Two opposing interest groups choose which decision-maker they want to target with their resource provision, and their decision depends on the decision-makers' ideologies as well as the network structure. We characterize the lobbying strategies in various network settings and show that a higher resource flow as well as homophily reinforce decision-makers' ideological bias. We highlight that competing lobbyists' efforts do not neutralize each other and their payoffs and competitive advantages depend on the networks they face. Our findings are consistent with empirically established lobbying activities.
Keywords: D72; D78; D83; D85; 330; Networks; Lobbying; Targeting; Flow of resources; Ideology; Centrality; Homophily; Colonel Blotto; Externalities